Shelf Life of Chicken Samosa Incorporated with Custard Apple (Annona Squamosa) Peel Powder : doi: 10.5958/2581-6616.2021.00006.2 - Lonarkar, A. G.; Rathod, K. S.; Ambadkar, R. K.; Patil, P. S.; Dhagare, L. G. (Journal of Meat Science, 2022)
Very few studies have been documented regarding the use of natural antioxidants like Custard Apple Peel Powder (CPeP) in meat products over synthetic antioxidants (BHT). Therefore, the current study was aimed to evaluate the effect of CPeP on the shelf life of chicken Samosa. The smashed boiled potato (10%) was mixed with minced (6 mm) breast fillets along with an onion (20%), condiments, spices mix, and salt which were then cooked on the preheated pan with continuous stirring till the appearance of golden brown colour and used as filler material for samosa. Antioxidants of 1% CPeP and BHT@125 mg/kg were added separately as treatments. About 20g of samosa mixture was filled into each dough sheet in a triangular shape and stored under refrigeration (4±1°C) temperature. During the storage period of 12 days the pH, tyrosine, and peroxide value increased significantly (P<0.05) between the storage period and treatment groups with a marginal decrease in TBRAS, tyrosine and peroxide value in CPeP treated chicken samosa compared to the control and BHT treated products. The protein, moisture, and fat content of all the treated products decreased gradually over the storage period. However, Total plate and psychrophilic count were lowest in CPeP treated product indicating the replacement of synthetic antioxidant (BHT) by 1% CPeP (natural antioxidant) as a good alternative in meat products.